Pelvic nerve injury causes a rapid decrease in expression of choline acetyltransferase and upregulation of c-Jun and ATF-3 in a distinct population of sacral preganglionic neurons - Peddie, Christopher J.; Keast, Janet R. (Frontiers in Neuroscience, 2011)
Autonomic regulation of the urogenital organs is impaired by injuries sustained during pelvic surgery or compression of lumbosacral spinal nerves (e.g. cauda equina syndrome). To understand the impact of injury on both sympathetic and parasympathetic components of this nerve supply, we performed an experimental surgical and immunohistochemical study on adult male rats, where the structure of this complex part of the nervous system has been well defined. We performed unilateral transection of pelvic or hypogastric nerves and analysed relevant regions of lumbar and sacral spinal cord, up to four weeks after injury. Expression of c-Jun, the neuronal injury marker activating transcription factor-3 (ATF-3), and choline acetyltransferase (ChAT) were examined. We found little evidence for chemical or structural changes in substantial numbers of functionally related but uninjured spinal neurons (e.g. in sacral preganglionic neurons after hypogastric nerve injury), failing to support the concept of compensatory events. The effects of injury were greatest in sacral cord, ipsilateral to pelvic nerve transection. Here, around half of all preganglionic neurons expressed c-Jun within one week of injury, and substantial ATF-3 expression also occurred, especially in neurons with complete loss of ChAT-immunoreactivity. There did not appear to be any death of retrogradely labelled neurons, in contrast to axotomy studies performed on other regions of spinal cord or sacral ventral root avulsion models. Each of the effects we observed occurred in only a subpopulation of preganglionic neurons at that spinal level, raising the possibility that distinct functional subgroups have different susceptibility to trauma-induced degeneration and potentially different regenerative abilities. Identification of the cellular basis of these differences may provide insights into organ-specific strategies for attenuating degeneration or promoting regeneration of these circuits after trauma.